Contemporary expectations of Polish small town authorities towards the state policy of local development - Sztando, Andrzej (Współczesne oczekiwania władz lokalnych małych miast wobec państwowej polityki rozwoju lokalnego, 2019)
The article is devoted to the issue of stimulating local development (LD). Its purpose is to present contemporary expectations of small town authorities towards the Polish state’s local development policy. The introductory part is devoted to the key categories: LD and local development policy. The desirable features of the state’s local development policy were also discussed. The identified expectations were divided into main groups: stopping activities interpreted as limiting territorial self-governance, changing the distribution of aid funds, the multidimensional reform of the self-government finance system, as well as improving the municipal instruments to stimulate LD. Within each group, specific expectations identified were discussed. An additional group of other expectations, characterized by a high level of diversity, was also distinguished and discussed. The research was carried out using a diagnostic survey method with the standardized long personal interview technique in 2019
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 5, s. 188-199
Keywords: local development; public governance; state policy; self-government; Poland; rozwój lokalny; zarządzanie publiczne; państwowa polityka; samorząd terytorialny; Polska